Global Simulations of Gravitational Instability in Protostellar Disks with Full Radiation Transport. II. Locality of Gravitoturbulence, Clumpy Spirals, and Implications for Observable Substructure - Wenrui Xu; Yan-Fei Jiang; Matthew W. Kunz; James M. Stone (The Astrophysical Journal)
Spiral perturbations in a gravitationally unstable accretion disk regulate disk evolution through angular momentum transport and heating and provide an observational signature of gravitational instability (GI). We use global 3D simulations to systematically characterize and understand these spiral perturbations. The spiral perturbations and the resulting transport are overall insensitive to the cooling type, with the exception that radiative cooling, especially in the optically thick regime, reduces the amplitude of temperature perturbations. Spiral perturbations are localized around corotation, allowing transport to be approximated by a local α viscosity to zeroth order in aspect ratio ( H / R ), but only after averaging over multiple orbits in time and/or multiple scale heights in space. Meanwhile, large-amplitude perturbations from strong gravitoturbulence can cause ${ \mathcal O }({α }^{1/2})$ deviation in the cooling rate of the disk. We develop empirical prescriptions for the angular momentum transport, heating, and cooling in a gravitoturbulent disk that capture the deviation from a viscous, unperturbed disk to first order in H / R and α ^1/2 . The spiral perturbations in saturated gravitoturbulence are clumpy, with dense clumps forming through the nonlinear coupling between multiple modes at different m . Observationally, the clumpy gravitoturbulence produced by saturated GI can be mistaken with observational noise or embedded companions, especially under finite resolution. Meanwhile, grand-design spirals with m -fold symmetry may be uncommon among disks in saturated gravitoturbulence, and we speculate that they may instead be a signature of recently triggered or decaying GI.